Time Pressure and Reduced Audit Quality Behavior: A Meta-Analysis - Mukhlas Adi Putra; Tarmizi Achmad (Academic Bright Collaboration, 2026)
Purpose - This study meta-analyses the relationship between time pressure and reduced audit quality behavior (RAQB) in external auditing, focusing on how deadline-related pressure contributes to behaviors that may weaken audit quality. Method - A PRISMA-informed search was conducted across Scopus, Emerald, EBSCOhost, ProQuest, ScienceDirect, Google Scholar, and backward/forward reference checks. No start-year restriction was applied, and the final search update was completed in May 2026. From 236 identified records, 10 studies met the inclusion criteria for quantitative synthesis after retrieval, screening, classification, and detailed coding. Effect sizes were harmonized into Pearson correlations and pooled using a random-effects model. Findings - The meta-analysis shows a positive association between time pressure and RAQB-related outcomes, with a pooled effect size of r = 0.247, 95% CI [0.198, 0.295], based on 10 studies and 1,634 observations. Heterogeneity is low (I² = 8.3%), indicating relatively consistent effects across the included studies. Sensitivity analyses, prediction interval estimation, Egger diagnostics, and fail-safe N assessment support a cautious but stable conclusion that time pressure is associated with higher likelihood of audit quality-reducing behavior. Research limitations - The focus on external auditors improves construct validity but limits broader moderator analysis and causal interpretation. Some studies report path coefficients rather than zero-order correlations, so the pooled estimate should be interpreted carefully. Originality - This study differs from broader audit-quality reviews by isolating direct evidence on RAQB, RAQP, AQRB, and DAB, thereby estimating the behavioral channel through which time pressure threatens audit quality.